2013
DOI: 10.1002/asia.201300450
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Organocatalytic Domino Michael/Aldol Reactions: An Efficient Procedure for the Stereocontrolled Construction of 2H‐Thiopyrano[2,3‐b]quinoline Scaffolds

Abstract: An efficient procedure for the stereocontrolled construction of 2H-thiopyrano[2,3-b]quinoline scaffolds has been developed, starting from simple compounds. The domino Michael/aldol reactions between 2-mercaptobenzaldehydes and enals, promoted by chiral diphenylprolinol TMS ether, proceed with excellent chemo- and enantioselectivity to give the corresponding synthetically useful and pharmaceutically valuable 2H-thiopyrano[2,3-b]quinolines in high yields with 90-99 % ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Recently, Y. Wang, Zhou, and co-workers published an efficient domino sulfa-Michael/aldol reaction of 2-mercaptoquinoline-3-carbaldehydes 131 with enals 137 catalyzed by the diphenylprolinol TMS ether XLIII (Scheme 63). 98 74%) and high enantioselectivities (90−96% ee). However, when a base was used as an additive instead of an acid, diastereomerically pure isomeric tetrahydrothiophenes 155 were obtained in moderate yields (43−66%) and moderate to good enantioselectivities (64−80% ee).…”
Section: Amino Catalysis Via Iminium Activationmentioning
confidence: 99%
“…Recently, Y. Wang, Zhou, and co-workers published an efficient domino sulfa-Michael/aldol reaction of 2-mercaptoquinoline-3-carbaldehydes 131 with enals 137 catalyzed by the diphenylprolinol TMS ether XLIII (Scheme 63). 98 74%) and high enantioselectivities (90−96% ee). However, when a base was used as an additive instead of an acid, diastereomerically pure isomeric tetrahydrothiophenes 155 were obtained in moderate yields (43−66%) and moderate to good enantioselectivities (64−80% ee).…”
Section: Amino Catalysis Via Iminium Activationmentioning
confidence: 99%
“…The chiral pyrrolidine 110 catalyzed domino reactions between thiosalicylic aldehyde and α,β‐unsaturated aldehydes proceeded with high chemo‐ and enantioselectivities to give thiochromene‐3‐carbaldehyde 111 in high yields with 91–98 % ee . The substrates initially formed Michael/aldol products, which underwent spontaneous dehydration to afford chiral thiopyrano[2,3‐ b ]quinolines with one new stereocenter …”
Section: Benzaldo‐x Bifunctional Building Blocks and Their Heterocyclmentioning
confidence: 99%
“…Uniting unique activation modes of N-heterocyclic carbene (NHC) catalysts with the concept of domino reactions, a new fast-growing field came into the spotlight in last couple of years or so [267][268][269]. Domino Michael/aldol reaction between 2-mercaptoquinoline-3-carbaldehydes and enals was catalyzed by diphenylprolinol silyl ether producing 2H-thiopyrano[2,3-b]quinolines in excellent yields and enantioselectivities [270]. Zhao et al reported studies on "cooperative NHC and rutheniun redox catalysis" in the oxidative esterification of aldehydes [271].…”
Section: Oxazaborolidines Chiral Oxazaborolidines (Known Asmentioning
confidence: 99%